Akuntansi Musyarakah dalam Perspektif Syariah dan PSAK 106 - Maujud, Junsi; Umasugi, Nirwan (Peneliti.net, 2026)
Musyarakah is a partnership contract in Islamic economics based on the principle of profit and loss sharing, in which profits are distributed according to an agreed ratio, while losses are borne proportionally to the contributed capital. The implementation of this contract requires an accounting system that is able to preserve sharia principles, transparency, and fairness among partners. This study aims to analyze the application of musyarakah accounting from the perspective of Islamic accounting and fiqh muamalah with reference to PSAK 106. This research employs a qualitative approach through a literature review by examining classical and contemporary fiqh literature, Islamic accounting standards, and previous related studies. The findings indicate that normatively PSAK 106 is in line with sharia principles, particularly in terms of recognition, measurement, presentation, and disclosure of musyarakah as a partnership-based contract. However, in practice, there are still challenges in consistently implementing the profit and loss sharing principle. Therefore, strengthening the understanding of Islamic accounting, enhancing sharia supervision, and increasing institutional commitment are necessary to ensure that musyarakah accounting functions effectively in realizing justice and economic welfare.